The Effect of Interbank Mudharabah Investment Certificate (SIMA) and Sharia Bank Indonesia Certificate (SBIS) on Liquidity in Sharia Commercial Banks - Rahmat, Ali; Hasan, Asya (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
This study aims to determine the effect of Interbank Mudharabah Investment Certificates (SIMA) and Bank Indonesia Syariah Certificates (SBIS) on Liquidity in Islamic Commercial Banks partially and to determine the effect of SIMA and SBIS on Liquidity in Islamic Commercial Banks simultaneously. This study uses a quantitative approach in the form of financial ratios based on time series. The data used is monthly data. The results of this study indicate that SIMA has no effect on liquidity at Islamic Commercial Banks for the 2016-2019 period, SBIS has no effect on liquidity in Islamic Commercial Banks for the 2016-2019 period, SIMA and SBIS have no simultaneous effect on liquidity in Islamic Commercial Banks for the 2016-2019 period.